Six Sigma methodology to evaluate and improve the results of three parameters of clinical chemistry evaluation quality assessment - Alberto, Ana Patrícia (2021)
From the PNAEQ’s Clinical Chemistry Program, three analytes were chosen to evaluate the quality assessment Total Cholesterol, LDL Cholesterol and Triglycerides Results from 2018 to 2020 were studied in order to evaluate and develop actions that allow the participants to reduce the variability of the results and improve their Sigma quality level in order to provide a better service to the patients.